DETERMINAN STRUKTUR MODAL DINAMIS : STUDI EMPIRIS DI BURSA EFEK INDONESIA - Widodo, puwanto (inovator, 2019)
Research on dynamic capital structure basically wants to know the existence of targeted leverage as hypothesized by Trade-Off Theory and Speed off Adjustment (SOA). Later developments, the magnitude of the speed of adjustment can be used as a determinant of capital structure theory used by the company. Another problem in dynamic capital structure research is the use of analytical tools that can produce biased and inconsistent predictors. To overcome this, this study uses dynamic panel data with the General Method of Moment (GMM) approach. Samples were taken from non-financial companies listed on the Indonesia Stock Exchange in the 2009-2015 period. The results of the inference show the existence of Dynamic Trade Off Theory and the variables of company characteristics and macroeconomic significantly influence the dynamic capital structure. In addition, it is known that there is an influence of company size and growth Opportunity on the speed of adjustment. Another finding is that he knows that managing profitability follows and Pecking Order Theory.Keywords : capital structure, static model, dynamic model